Chromaticity Of Bipartite Graphs With Three And Four Edges Deleted - Yeang , Hoong Phoy (2007)
Graphs are a set of vertices and edges. All vertices may or may not be joint. Vertex coloring is the coloring of a graph with a fixed number of colors such that adjacent vertices are of different colors.